La calidad del desempeño de los comités de gestión escolar y su influencia en el cumplimiento de los compromisos de gestión escolar de las instituciones educativas públicas urbanas secundarias de la Ugel Maynas 2023 - Diaz Armas, Alix Christina (2025)
This study primarily aims to investigate the influence of the quality of performance of School Management Committees on the fulfillment of School Management Commitments in urban public secondary schools within the Maynas Local Educational Management Unit (UGEL) in 2023. Classified as a basic research study, it seeks to generate new knowledge in a context where similar studies are scarce. Methodologically, a non-experimental quantitative design was employed, using a survey administered to the directors of 91 educational institutions as the data collection instrument. Statistical analysis, measured by the Nagelkerke index, did not reveal a significant relationship between the overall performance of SMCs and the global fulfillment of SMCs (Nagelkerke = 0.709; p > 0.05). However, upon analyzing the specific objectives, a significant relationship was found between the performance of the Operations Management Committee and the fulfillment of SMC 3 (Nagelkerke = 0.498; p < 0.05), the performance of the Pedagogical Management Committee and the fulfillment of SMC 4 (Nagelkerke = 0.484; p < 0.05), and the performance of the Welfare Management Committee and the fulfillment of SMC 5 (Nagelkerke = 0.451; p < 0.05). These findings suggest that while the overall performance of SMCs does not significantly impact the global fulfillment of commitments, there is a significant influence between the specific performance of each committee and the fulfillment of commitments associated with their respective areas of competence.